EVALUATION OF EFFECTIVENESS OF MORINGA'S LEAVES AGAINST Escherichia coli USING DISC DIFFUSION METHOD - Dhillon, Erin; Rotua, Margaretia Yenni; Khu, Adrian; Sinaga, Ade (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2021)
The UPTD Puskesmas annual report book in Medan Tembung District reported that the number of diarrhea sufferers had increased every year. Moringa plants have many benefits, both leaves, flowers, stems, fruit blossoms, and seeds. The moringa leaves contain various phytochemicals, viz. alkaloids, flavonoids, phenols, steroids, triterpenoids, and tannins, which have antimicrobial properties. This study aimed to determine the antimicrobial effect of the ethanol extract of Moringa leaves against Escherichia coli. This study was an experimental study with a posttest only control group design model. The method used to evaluate ethanol extract's anti-bacterial effect from Moringa leaves was the disc diffusion method. Moringa leaf extract was obtained by maceration method with a ratio of Simplicia powder, and ethanol solvent was 1:10. The ethanol extract was then concentrated by rotary evaporator and diluted using DMSO into five different concentrations viz. 70%, 75%, 85%, 90%, and 95%. All data were analyzed by the One Way Anova test and expressed as Mean Â± SD. This study showed that all treatment groups in this study had a significant difference in the zone of inhibition; it was shown by the P-value <0.05. Only 70% of concentrations from Serial concentration of extract were significant differences against the positive control. Overall, it can be concluded that the ethanol extract of moringa leaves is effective as an anti-bacteria against Escherichia coli, especially at concentrations > 75%.